Initial Changes in the Heart Conduction System Illustrated by Difference Map Patterns in Adolescent Patients After Kidney Transplantation: A Pilot Study - Laszki-Szcząchor, K.; Zwolińska, D.; Sobieszczańska, M.; Szcząchor, K.; Makulska, I.; Polak-Jonkisz, D. (Transplantation proceedings, 2018)
Cardiovascular complications (CVCs) in patients with end-stage renal disease (ESRD) often require hospitalization and are associated with an increased risk of fatality. Although kidney transplantation (KTx) improves a patient's status, CVCs are still a serious risk factor, so early identification is very important for final therapeutic outcome. This study included 5 post-KTx patients (age, 20.8 ± 1.16 years), dialyzed before KTx, and followed up for 6.7 ± 1.71 years. Body surface potential mapping (BSPM) was performed 4 times: twice before and twice after KTx. Electrocardiographic data were processed into map plotting to illustrate differences in ventricular activation times (VATs). A comparative analysis of difference maps, both of dialyzed patients and normal subjects, highlighted certain specificities in the distribution of VAT changes for the left anterior fascicle block (LAFB). The maps clearly showed a significant correlation between the intensity of changes and duration of dialysis before KTx. After KTx, VATs seemed to be similar to those in normal subjects; however, this was true only for patients dialyzed for <1 year. The patients dialyzed for >1 year showed persistent conduction abnormalities on their VAT maps. Summary differences in VAT maps can enable diagnostics of initial activation propagation abnormalities in the heart. Short-term dialysis therapy before KTx imposes positive effects with regression of heart conduction changes. These observations need to be verified in a larger study population. •There were differences in the distribution of ventricular activation time maps in hemodialysis patients.•The changes for the left anterior fascicle block of the His bundle.•There were significant correlation between the intensity of changes and the duration of dialysis before kidney transplant.